PENGARUH GOOD CORPORATE GOVERNANCE, KUALITAS AUDIT DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris Perusahaan Properti dan Real Estate listing di Bursa Efek Indonesia) - Heni Pujiastuti (Aliansi : Jurnal Manajemen dan Bisnis, 2018)
This study aims to examine the effect of good corporate governance, audit quality, and size company against earning management. Data used in this study is annual report and audited financial report from each company, published through website www.idx.co.id. The sample used in this study are property and real estate companies listed in Indonesian Stock Exchange (IDX) during 2013 up to 2015 resulted 96 observations. The Study shows that audit quality has the significant and negative impact toward earning management. While independent commissioner, institutional shares, managerial shares and size company haven’t significant effect toward earning management.